2011
DOI: 10.1128/jvi.01278-09
|View full text |Cite
|
Sign up to set email alerts
|

The Tyro3 Receptor Kinase Axl Enhances Macropinocytosis of Zaire Ebolavirus

Abstract: Axl, a plasma membrane-associated Tyro3/Axl/Mer (TAM) family member, is necessary for optimal Zaire ebolavirus (ZEBOV) glycoprotein (GP)-dependent entry into some permissive cells but not others. To date, the role of Axl in virion entry is unknown. The focus of this study was to characterize entry pathways that are used for ZEBOV uptake in cells that require Axl for optimal transduction and to define the role of Axl in this process. Through the use of biochemical inhibitors, interfering RNA (RNAi), and dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
182
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(193 citation statements)
references
References 76 publications
(96 reference statements)
11
182
0
Order By: Relevance
“…It has been shown that the activation of certain RTKs may trigger the specific induction of clathrinmediated endocytosis, as reviewed in reference 2, while the activation of other RTKs is known to trigger actin reorganization and the induction of macropinocytosis through the Rab5 GTPase (3,18,27). Hunt and colleagues (21) have shown that the activation of the RTK Axl specifically enhances the macropinocytotic uptake of the filamentous Ebola virus (21). Additionally, it has been shown that clathrin-independent entry of influenza virus requires Ras-PI3K signaling, a pathway that can be activated by certain RTKs and can signal the activation of macropinocytosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the activation of certain RTKs may trigger the specific induction of clathrinmediated endocytosis, as reviewed in reference 2, while the activation of other RTKs is known to trigger actin reorganization and the induction of macropinocytosis through the Rab5 GTPase (3,18,27). Hunt and colleagues (21) have shown that the activation of the RTK Axl specifically enhances the macropinocytotic uptake of the filamentous Ebola virus (21). Additionally, it has been shown that clathrin-independent entry of influenza virus requires Ras-PI3K signaling, a pathway that can be activated by certain RTKs and can signal the activation of macropinocytosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is an important entry pathway for a growing number of predominantly larger viruses, such as poxviruses, filoviruses, IAV, adenovirus and HIV1 (Brindley et al, 2011;Callahan et al, 2003;de Vries et al, 2011;Hunt et al, 2011;Mercer and Helenius, 2008;Nanbo et al, 2010;Saeed et al, 2010;Shimojima et al, 2006). As already mentioned, the process involves the activation of a complex signaling pathway that transiently modifies the dynamics of the actin cytoskeleton.…”
Section: Endocytosismentioning
confidence: 99%
“…The signaling pathways are best characterized for viruses that trigger plasma membrane ruffling and macropinocytosis for endocytic uptake. These include vaccinia virus (VACV), Ebola virus, Kaposi's sarcoma-associated herpesvirus (KSHV), adenovirus and influenza A virus (IAV) (Amstutz et al, 2008;Brindley et al, 2011;Chakraborty et al, 2011;de Vries et al, 2011;Eierhoff et al, 2010;Hunt et al, 2011;Kälin et al, 2010;Meertens et al, 2012;Meier et al, 2002;Mercer and Helenius, 2008;Nanbo et al, 2010;Raghu et al, 2009;Saeed et al, 2010;Schmidt et al, 2011;Shimojima et al, 2006;Valiya Veettil et al, 2010).…”
Section: Signalingmentioning
confidence: 99%
“…However, the direct interaction of these kinases with GPs has never been proven [29]. Therefore, these kinases are thought to promote macropinocytosis, resulting in enhanced filovirus infection [30] (Fig. 2b).…”
Section: Entrymentioning
confidence: 99%